Incentives and the Role of Institutions in the Provision of Social Safety Nets - Weigand, Christine (World Bank, Washington, DC, 2012)
The institutional environment can determine the effectiveness and efficiency of social safety net programs. An otherwise perfectly designed program may fail if it does not take into account the role of the different institutional actors, and the incentives they face in the implementation and delivery of the program. Thus, incentive structures-between sponsors (i.e., governments) and providers, and between providers and their clients-play an important role in determining the success of a social safety net program. The biggest challenges in countries with fully developed institutions tend to be: 1. Optimizing program mix: With many and very sophisticated programs, it is crucial to determine the 'right' program mix and reduce overlap and conflicts between social programs. Regular monitoring and evaluation play a central role in achieving this. 2. Deciding on the degree of devolution: Local authorities can be better informed and more accountable to their local constituencies. Nevertheless, the devolution of certain policy decisions not only requires a certain level of capacity at the local level, but must also be based on an explicit, clearly defined contract between the central and local governments.